Xrd Analysis Of Cu-Ai Interconnerct Intermetallic Compound In An Annealed Micro-Chip - Thangaraj, Joseph Sahaya Anand; Chua, Kok Yau; Hng, May Ting; Lee, Cher Chia (2012)
Cu-A1 intermetallic compound (IMC) in Cu wire-A1 bond pad interconnect interface is drawing attention of researches. However, due to thin IMC thickness, the characterizations of the IMC are limited to expensive and time consuming techniques. An evaluation is performed to use common X-Ray Diffraction (XRD) technique to identify the IMC in the Cu wired micro-chip samples in powder form. Existence of mixture of CuA1 and CuA12 was first confirmed by transmission electron microscope (TEM) and energy dispersive X-ray (EDX). In XRD analysis, peak correspond to CuA1 phase is identified from measurement with slower scan configurarion. The difficulty for IMC peak detection in diffractogram is due to low composition ratio of IMC relative to other materials available in the sample. KOH treatment for enhancing IMC peaks intensity does not work as expected as it etches the IMC as well.